Searching for G-Quadruplex-Binding Proteins in Plants: New Insight into Possible G-Quadruplex Regulation - Volná, Adriana; Bartas, Martin; Nezval, Jakub; Špunda, Vladimír; Pečinka, Petr; Červeň, Jiří (Biotech (Basel (Switzerland)), 2021)
G-quadruplexes are four-stranded nucleic acid structures occurring in the genomes of all living organisms and viruses. It is increasingly evident that these structures play important molecular roles; generally, by modulating gene expression and overall genome integrity. For a long period, G-quadruplexes have been studied specifically in the context of human promoters, telomeres, and associated diseases (cancers, neurological disorders). Several of the proteins for binding G-quadruplexes are known, providing promising targets for influencing G-quadruplex-related processes in organisms. Nonetheless, in plants, only a small number of G-quadruplex binding proteins have been described to date. Thus, we aimed to bioinformatically inspect the available protein sequences to find the best protein candidates with the potential to bind G-quadruplexes. Two similar glycine and arginine-rich G-quadruplex-binding motifs were described in humans. The first is the so-called "RGG motif"-RRGDGRRRGGGGRGQGGRGRGGGFKG, and the second (which has been recently described) is known as the "NIQI motif"-RGRGRGRGGGSGGSGGRGRG. Using this general knowledge, we searched for plant proteins containing the above mentioned motifs, using two independent approaches (BLASTp and FIMO scanning), and revealed many proteins containing the G4-binding motif(s). Our research also revealed the core proteins involved in G4 folding and resolving in green plants, algae, and the key plant model organism, Arabidopsis thaliana. The discovered protein candidates were annotated using STRINGdb and sorted by their molecular and physiological roles in simple schemes. Our results point to the significant role of G4-binding proteins in the regulation of gene expression in plants.
Keywords: G-quadruplex resolving; NIQI; RGG motif; G-quadruplex-binding proteins; regulation of gene expression; G-quadruplex folding